Symptomatic Orthotopic Ureterocele in a Dog - Abibe, Rebeca Bastos [UNESP]; Seullner Brandao, Claudia Valeria [UNESP]; Pereira, Geovane Jose [UNESP]; Mesquita, Luciane dos Reis [UNESP]; Rahal, Sheila Canevese [UNESP] (Univ Fed Rio Grande Do Sul, 2020)
Background: Ureteroceles are cystic dilatations of the terminal ureter and is a rare diagnosed condition in dogs. They can be classified as orthotopic when it is entirely within the bladder and the ureteral orifice emerges normally or ectopic if the ureteral orifice is not in the normal position in the trigone. Orthotopic are usually clinically silent. Ureterocele can contribute to lower urinary tract disease leading to infections and loss of the renal function. As long as this injury can arise slowly, it might be underdiagnosed in companion animals. This case aims to report a case of a bitch with diagnosed symptomatic orthotopic ureterocele efficacious surgical treatment. Case: A 5-month-old female mixed breed was referred to the veterinary hospital, with a major complaint of urinary incontinence since the birth date after the first attendance in a colleague who have suspected of ureterocele considering ultrasound report of a vesicle of 1.4 x 1.5 cm in lefts ureter bladder's insertion topography with ipsilateral hydroureter and renal dilatation. Beside the urinary dysfunction, the animal presented good general status and normal vital signs. Complete blood count and biochemical analysis were within normal ranges. A new ultrasound exam and Computerized Urotomography with contrast gave the definitive diagnosis of left orthotopic ureterocele with twisted hydroureter (proximal 1.29 cm and distally 0.98 cm) and hydronephrosis (3.32 cm). The marsupialization was chosen scientifically based to correct the ureterocele and the patient presented good general condition since then with prompt improvement of clinical signs. The patient was submitted to serial image exams in six weeks following up to check the consequent urinary tract dilatation from the previous disease regression. After the last follow up animal received hospital discharge and was assessed twice in four months with normal measures of the urinary tract. Discussion: Different from the most common insert point of this injury, this case report presents an orthotopic ureterocele which due to the clinical signals, could be diagnosed differently from the literature who have described most often ectopic or asymptomatic events. Corroborating with usual development of uretero vesical junction obstruction described, this patient also advanced to hydroureter, hydronephrosis and kidney parenchymal loss. Due to being uncommon in small animal routine, diagnosis and therapeutic recommendations are based on few veterinarian and mainly human data. The gold-standard diagnostic method is excretory urethrocystography with an intra-bladder image called cobra-head or a contrast cystic fill defect. When ectopic ureterocele is suspected, intra-venous contrast urography or Computerized urotomography are a thrustful choice. Surgical treatment is indicated in symptomatic and obstructive ureterocele. The planning was based in urotomography diagnosis of unilateral orthotopic left ureterocele, marsupialization technique was performed. Two days after the procedure, the patient returned maintaining the total enhancement of incontinence. During the image follow up made after the surgery was observed decrease of the dilatations and improvement of renal medullary cortical ratio. This case report raises the importance of counting uncommon diseases as differential diagnosis in the veterinarian routine. Also, the use of the correct image approach can lead to the definitive diagnosis and treatment.
Keywords: incontinence; urology; surgery; dog